CD4-/CD56+/CD123+ Hematodermic Neoplasm Showing Early Liver Metastasis - Choi, Kyu-Won (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2010)
Hematodermic neoplasm (HN) is a clinically aggressive neoplasm with a high incidence of cutaneous involvement and a risk of leukemic dissemination. In the recent WHO-EORTC classification, the term blastic natural killer cell lymphoma has been replaced with CD4+/CD56+ HN because of its derivation from a plasmacytoid dendritic cell precursor. Cases of HN that completely lack CD4 or CD56 expression, therefore represents a diagnostic problem. A 68-year-old Korean male was diagnosed with CD4-/CD56+ HN and treated with hyper-CVAD (cyclophosphamide, vincristine, doxorubicin, dexamethasone) at initial treatment, and then switched to high dose methotrexate/cytarabine. His disease relapsed and resulted in death from bone and brain disease 6 months after complete clinical remission, despite diagnostic workups, including a radioisotope liver scan and ultrasound-guided fine needle aspiration biopsy. Further cytogenetic studies such as comparative genomic hybridization could elucidate the genetic mechanisms in the development and progression of lymphomas. We report an unusual case of 'CD4-/CD56+/CD123+ HN' showing early liver metastasis.